The Student Movement as an Object of study in the Colombia and continental historiography: Notes for a balance and a research agenda (2011)
The events of 1968 are recognized today as the irst global Cultural Revolution. Latin America was not stranger to the big changes in a time known for cultural social movements and student protests. Today is not yet known a balance about the Continental Historiography of this event. This article attempts to point out the limitations of scientiic research in Colombia, marked by their fragmented and dispersed character. In a continental level are explored the cases of Mexico,Argentina and Brazil in order to approach currents and looks beyond the national borders which renew and contextualize our work. In this way, it seeks to help in the construction of a historiography map to locate the new generations of researchers interested in the student movement in order to consolidate an area of research and relection at the national level.